Introduction to and Discussion Summary of Ching-hsien Wang's "Cheng Hsuan Awakened from a Dream" - Adams, Hazard (Surfaces)

(untitled) (Les Presses de l’Université de Montréal, 1995)
In the context of the Second International Conference on Humanistic Discourse, this text introduces Ching-hsien Wang's "Cheng Hsuan Awakened from a Dream" and reports on the central concerns that emerged in its discussion.